The Maxims Violation Of Cooperative Principles In The Movie Entitled The Adam Project - Gek Wulan Novi Utami; Cakra Sagiarta Lee; Trisha Endah Setiawati; Ni Luh Desy Suari Dewi; I Gede Neil Prajamukti Wadhana (Denpasar Institute, 2023)
In pragmatic research, conversations or utterances are important things to pay attention to because the speakers' use of language has an impact. Interestingly, the communication that we do usually does not necessarily follow the rules of maxims so we get the result of violating the rules of maxims. This study analyzed the detailed factor of violation and flouting of maxims which affect the way people communicate on a daily basis which are quietly violating to misleading, opting out, clashing, and flouting. This study utilized the qualitative method with the total of 17 data combined on each of the maxims acquired through the movie The Adam Project and analyzed by utilizing the theory of Cooperative Principle and Maxims. The results indicated that data about all types of maxim are found and for quantity and relation maxims, both are mostly violated by quietly violating to reach misleading purposes whereas quality and manner tend to be flouted to create conversational implicature, which the hearer should make an effort to understand the utterance